THE IMPORTANCE OF CULTURE IN TEACHING FOREIGN LANGUAGES (Konferensiyalar | Conferences, 2024)
Culture is important in the process of teaching foreign languages because it adds context and depth to the learning experience. As a result, culture is an important issue for any educator concerned with their student's academic performance because it has a direct impact on the lesson process. The appropriate attitude towards pupils' cultural views should be fostered to compromise with them. This article will explore the importance of culture in teaching foreign languages, proving it by citing scientific sources and investigating the value of incorporating cultural components into language instruction to improve students' grasp and appreciation of the target language.